Development of fluorescence based DNA biosensor utilizing quantum dot for DNA of Ganoderma boninense - Mohd Bakhori, Noremylia (2013)
In this work, fluorescence based DNA biosensor has been developed for detection of ganoderma boninense utilizing quantum dot as sensing material. The DNA sensor was fabricated by modification of hydrophobic surface of CdSe/ZnS quantum dot (CdSe/ZnS QD) nanoparticle with mercaptopropionic acid (MPA) to form water-soluble CdSe/ZnS QD. The modified CdSe/ZnS QD was successfully attached to the ssDNA to form CdSe/ZnS QD-ssDNA conjugate. Attachment of CdSe/ZnS QD with ssDNA and hybridization procedures are divided into procedure 1 and 2. Hybridization of complementary target DNA with CdSe/ZnS QD-ssDNA conjugate and reporter probe labeled with Cy5 is monitored using fluorescence resonance energy transferred (FRET) as detection mode. The FRET of CdSe/ZnS QD-dsDNA is distinguishable from CdSe/ZnS QD-ssDNA conjugate based on no FRET was observed without target DNA system. Several parameters were studied to determine the optimum conditions of hybridization efficiency including hybridization time and hybridization temperature. The highest FRET intensity was observed at 10 minutes hybridization with hybridization temperature of 45 °C for procedure 1 and 25 °C for procedure 2. For sensitivity study, decreased of FRET intensity was observed when the concentration of target DNA increased. Limit of detection (LOD) for procedure 1 is 2.4x10-13 M and procedure 2 is 1.12x10-12 M. Selectivity study for the developed system confirmed that non-complementary DNA shows no FRET signal but only emission of QD. The hybridization did not occur due to QD was not in position with reporter probe for FRET process to occur. This proved that the detection system specific towards target DNA. Reproducibility shows acceptable relative standard deviation (R.S.D) of 1.67 % (n=5) and 0.86 % (n=5) for procedure 1 and 2 respectively. In TEM characterization, the particle size of CdSe/ZnS QD and CdSe/ZnS QD-ssDNA conjugate is within the range of 2 to 10 nm. Agglomeration was observed for CdSe/ZnS QD-ssDNA conjugate.